An evolutionary approach to low-level conversational cooperation. (September 2017) - Wacewicz, Sławomir; Żywiczyński, Przemysław; Chiera, Alessandra
Abstract: The cooperative character of language is an empirical fact and one of the key tenets in linguistics. However, this cooperative character is what makes it evolutionarily suspect: under normal circumstances sharing honest information with biologically unrelated individuals and without any obvious costs is not an ESS (evolutionarily stable strategy) and is not expected to evolve. Here we approach this problem in the context of prototypical language use (also evolutionarily), that is face-to-face conversation, a multimodal interaction unfolding in real time that involves a complex interplay between embodied agents in spatial proximity. We focus our review on low-level coordinative processes – examples being proxemic alignment or postural mirroring – to a large degree continuous with what is found in non-human primates. We aim at categorisation and terminological clarification of these processes, which in turn helps us evaluate their role in initiating and maintaining cooperatively oriented communicative interaction. We conclude with suggesting ways in which such low-level coordinative processes might have formed an evolutionary basis for cooperation, with a focus on the possible role of TFT (tit-for-tat) and TFT-like strategies. Highlights: "Cooperation" is an evolutionarily interesting problem only when defined in game-theoretic terms. In face-to-face conversation, individuals coordinate, and cooperate, on multiple levels. These can be analytically distinguished into "higher" and "lower" levels. Low-level coordination phenomena facilitate cooperation by establishing and sustaining interactional focus.